2016
DOI: 10.1515/hukin-2015-0147
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Physiological Responses to Interval Training in Cyclists With and Without Interval Training Experience

Abstract: The aim of this study was to determine differences in glycolytic metabolite concentrations and work output in response to an all-out interval training session in 23 cyclists with at least 2 years of interval training experience (E) and those inexperienced (IE) in this form of training. The intervention involved subsequent sets of maximal intensity exercise on a cycle ergometer. Each set comprised four 30 s repetitions interspersed with 90 s recovery periods; sets were repeated when blood pH returned to 7.3. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 34 publications
1
15
0
2
Order By: Relevance
“…In both SIE protocols, there were not any differences in peak power output. That indicates a lack of pacing strategy, which was reported in other researchers in sprint interval exercise session [25]. The PPO during SIE 6×10"/4' did not decrease, which indicated that a 4-min recovery was sufficient to restore peak power.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In both SIE protocols, there were not any differences in peak power output. That indicates a lack of pacing strategy, which was reported in other researchers in sprint interval exercise session [25]. The PPO during SIE 6×10"/4' did not decrease, which indicated that a 4-min recovery was sufficient to restore peak power.…”
Section: Discussionsupporting
confidence: 53%
“…Future studies should consider an individual approach to time and intensity of recovery in order to achieve adequate regeneration and the ability to reproduce peak power, total work and level of physiological response in subsequent series with similar RPE. One of the possible approaches is to control the return of pH (H + ion concentration) to the baseline level (>7.30), in accordance with Hebisz et al [25].…”
Section: Discussionmentioning
confidence: 90%
“…One key characteristic of the program is that the intervals were conducted at a regulated and controlled intensity, i.e., at a stipulated TPO during all the intervals, instead of exercise at subjective “maximum effort.” Most non-athletic individuals find it difficult to know how hard they can work during a supramaximal sprint (Hebisz et al, 2016). This is in line with our clinical experiences and experiences from research on physical performance and exercise training among older individuals (Rosendahl et al, 2006; Hedlund et al, 2012; Lindelöf et al, 2012; Jonasson et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A general problem with existing training protocols that limits their broad applicability is the lack of guidance for determining appropriate training intensity. Inexperienced non-athletes and older individuals appear to lack the experience needed for proper pacing at supramaximal intensities, leading to difficulties in finding an appropriate target intensity (Hebisz et al, 2016). In addition, even if the instruction is to exercise at a maximum effort in all-out sprints, pacing is used to end up with a sustainable and acceptable training intensity (Billaut et al, 2011; Hureau et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation